AN OBJECTIVE LOOK AT EFFECTS OF INCOME TAXES ON FINANCING SMALL BUSINESS. - McDonald, Roderick F. (The Accounting Review, 1955)
It is often suggested that the high income tax rates of modern times have exerted seriously repressive effects on growth of small business enterprises. The argument is that high income tax rates curtail the funds available to individuals and corporations for investment, thus reducing the amounts, which otherwise would be used to finance growing enterprises. In most cases, the primary source of increase in the owner's equity is reinvested earnings. Prospective outside investors with large incomes will be taxed at high rates on any profit they realize from investments in growing enterprises. Thus, there is danger that they would be discouraged from making investments of this sort. If income taxes have been restricting the growth of small enterprises, then it would appear that fundamental tax revision ought to be undertaken. This is an important question, but a very difficult one to investigate and dispose of, because of lack of objective evidence, which would prove what the nature, and extent of the effects have actually been.